Reduced Recombination and Capacitor-like Charge Buildup in an Organic Heterojunction - Ardalan Armin (Journal of the American Chemical Society, 2020)
Organic photovoltaic (OPV) efficiencies continue to rise, raising their prospects for solar energy conversion. However, researchers have long considered how to suppress the loss of free carriers by recombination—poor diffusion and significant Coulombic attraction can cause electrons and holes to encounter each other at interfaces close to where they were photogenerated. Using femtosecond transient spectroscopies, we report the nanosecond grow-in of a large transient 20 Stark effect, caused by nanoscale electric fields of ~487 kV/cm between photogenerated free carriers in the device active layer. We find that particular morphologies of the active layer lead to an energetic cascade for charge carriers, suppressing pathways to recombination, which is ~2000 times less than predicted by Langevin theory. This in turn leads to the build-up of electric charge in donor and acceptor domains—away from the interface—resistant to bimolecular recombination. 25 Interestingly, this signal is only experimentally obvious in thick films, due to the different scaling of electro-absorption and photo-induced absorption signals in transient absorption spectroscopy. Rather than inhibiting device performance, we show that devices up to 600 nm thick maintain efficiencies of > 8 % because domains can afford much higher carrier densities. These observations suggest that with particular nanoscale morphologies, the bulk heterojunction can go beyond its established role in charge photogeneration, and can act as a capacitor, where adjacent free charges are held away from the interface and can be protected from bimolecular recombination.